Effects of a service learning experience on confidence and clinical skills in baccalaureate nursing students. (February 2018) - Saylor, Jennifer; Hertsenberg, Lindsey; McQuillan, Malissa; O'Connell, Ashley; Shoe, Kimberly; Calamaro, Christina J.
Abstract: Background: Camp programs yield positive and lasting benefits for children. Integrating a summer camp into a nurse course with a service learning design fosters learning beyond the classroom and enhances community engagement. Objective: The purpose of this study is to describe the nursing students' experience and perceived confidence after completing a service learning nursing course. Design: This is a descriptive, qualitative research study that used reflection and a perceived confidence questionnaire. Setting: The study was conducted in a school of nursing and surrounding university campus facilities during the diabetes camp. Participants: The participants ( n = 23) were nursing students who enrolled in the nursing course. Methods: As part of the course requirements, students completed an eight item question confidence survey before and after the diabetes camp related to diabetes and camp management, and interpersonal abilities with patients, families, and healthcare professionals. Within 48–72 h after diabetes camp, the students completed the reflection paper. The pre and post Confidence Surveys were analyzed using a t -test and thematic analysis was used to analyze the reflection paper. Results: Overall, perceived confidence levels increased after completing the service learning course ( t = − 9.91, p = 0.001). Four themes emerged from the qualitative analysis: pre-camp assumptions and fears, growth in confidence, understanding diabetes management in the community, and appreciation for learning beyond the classroom and hospital setting. Conclusions: This service learning course provided nursing students the ability to not only develop diabetes clinical skills and perceived confidence, but also life skills including teamwork, leadership, and conflict resolution. Highlights: Service learning bridges the chasm between the classroom and "real life" clinical. Diabetes camp illustrates the daily challenges for children with and without diabetes. Teaching beyond the classroom fostered critical thinking and community engagement. Reflection analysis found that clinical, leadership, and personal attributes improved.